2019
DOI: 10.11648/j.ajmcm.20190403.13
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convective Magnetohydrodynamic Heat Transfer Flow of Williamson Fluid Over a Porous Wedge

Abstract: The present article examines the influence of thermal radiation on two-dimensional incompressible magnetohydrodynamic (MHD) mixed convective heat transfer flow of Williamson fluid flowing past a porous wedge. An adequate similarity transformation is adopted to reduce the fundamental boundary layer partial differential equations of Williamson fluid model in to a set of non-linear ordinary differential equations. The solutions of the resulting nonlinear system are obtained numerically using the fifth order numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Hence increase in buoyancy leads to an increase in the overall velocity of the flow but a decrease in the temperature of the flow. As earlier remarked in the introduction, these results supports the findings of [16,19,20].…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Hence increase in buoyancy leads to an increase in the overall velocity of the flow but a decrease in the temperature of the flow. As earlier remarked in the introduction, these results supports the findings of [16,19,20].…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Megaheed [18] considered Williamson fluid flow due to a nonlinear stretching sheet with viscous dissipation and thermal in the study viscosity and fluid conductivity are assume to vary with temperature and the noted that thermal radiation parameter and the Eckert number has an effect on the temperature distribution and thicken thermal region which leads to an increase in the local Nusselt number and decrease in local skin-friction coefficient while rise temperature is cause by an increase in both Williamson viscosity parameter. Panezai et al [19] examined the influence of thermal radiation on two-dimensional incompressible magneto-hydrodynamic mixed convective heat transfer flow of Williamson fluid flowing past a porous wedge on a non linear stretching surface and the free stream experiencing external forces on the fluid and it was concluded that non -dimensional velocity profile increases with an increase in wedge angle parameter while nondimensional temperature profile decrease with an increase in the wedge angle parameter ,nondimensional velocity deceases with an increase in magnetic parameter. Hashim et al [20]…”
Section: Introductionmentioning
confidence: 99%
“…They presented the effects on velocity and skin friction graphically by adopting the shooting technique. Panezai et al [8] numerically investigated the heat transfer characteristics of Williamson fluid over a porous Wedge. Salahuddin et al [9] studied the boundary layer phenomena of Williamson-type fluid with slip conditions over a stretching cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Another analytic investigation in this direction was suggested by Hayat et al 20 Another study reported by Kumar et al 21 conferred mixed convection aspects in the flow of a nanofluid over a vertical channel with help of Robin boundary conditions. Panezai et al 22 deliberated the mixed convection prospective in the Williamson fluid flow encountered by a porous wedge. The solution procedure is followed with the help of the Runge–Kutta–Fehlberg technique with considerable accuracy.…”
Section: Introductionmentioning
confidence: 99%